Makna Dan Motif Solidaritas Mercedes-Benz Club Bandung - Ghema Ajis Saputra; Catur Nugroho (Universitas Mataram, 2020)
During the research, the context of understanding as well as in point of focus in the minutely is the way society Mercedes-Benz Club Bandung represent a meaning and motives inside a attachment is a the community (automotive) and being affected as well as based on communication through symbols which is in shape and agreed on the interaction and daily life of the Mercedes-Benz Club Bandung community. In the discussion of the survey, researchers used with the approach phenomenology with contructivism paradigm, this context about a thing done by scientist is as the purpose of conducting by with analysis and withdrawal of meaning and chemical analysis with motives of symbolic communication to do something abaout community Mercedes-Benz Club Bandung in implying a meaning of “solidarity”. The process has been held by research by following a groove activities, daily activity, as well as any assembly or with schedule made by community. Research conducted by researchers by means of do something like making observation, interview at the field with several informants, and in-depth interview and pick up some field evidence through the actual shot and take a picture from field during the process activity by community. In this part from genereal community to Mercedes-Benz Club Bandung is an organization that have rules and regulation like another community in Indonesia. An explanation on this community specially to Mercedes-Benz Club Bandung formed by the same hobby, like have another people like in to automotive the basis and passion for love at automotive. Of the thing that the problem occurs meanings in this community the the problem occurs meanings arising from each of community member in the Mercedes-Benz Club Membership. In this parts about trough a process of solidarity in the form of motive and communication a solid passing symbols and in the midst of same perception with the union of the meaning of solidarity from activities of, interaction to a fellow member of a as well as the communities hit by effect of arising done by the community. Tag Line as well as community with vision and mission to Mercedes-Benz Club Bandung that is, “Proud-Loyalty-Fraternity” is one most of concrete manifestation and symbol with good attitude and interaction from in the community to internal from external community knew of the existence of that happened at community, one in which are a very positive and plain terms about the impact of to the people who can describe and evaluate the results of the thought which thinking from another people is in community from the surrounding to the Mercedes-Benz Club Bandung.